Lecturers' and students' perceptions on ethics in academia and lecturer-student interaction - Mohamed Saat, Maisarah; Mohd. Jamal, Noriza; Othman, Aniza (Faculty of Management and Human Resource Development, 2004)
Since faculty can strongly influence the overall ethical climate of the University environment (Schulte et.al 1991), the professional and ethical conducts of faculty are of special concern to the public. In general, the aim of this study is to investigate the perceptions of students and lecturers on ethics in academia and lecturer-student interaction. Lecturers of Fakulti Pengurusan dan Pembangunan Sumber Manusia, Universiti Teknologi Malaysia and final year students of the faculty and three other engineering faculties were randomly selected to answer the questionnaire on the subject. Results of the study reveal that lecturers perceive more actions as unethical than the students. Gender and academic program are found to be factors influencing students’ perceptions, but only in several situations. No demographic factors influence lecturers’ ethical perceptions. Results of this study disclose that students’ expectations on lecturers’ actions are higher regarding ethics. Respondents agree that the collective and individual action of a member in a university will affect the overall image of the University. Findings show that unethical actions that most lecturers do are using university equipment for personal activities, teaching material that the lecturers have not really mastered and canceling office hours excessively. The study found that the likeliness of respondents committing the unethical behaviour is rather low compared to the likeliness of their colleagues doing it. Among recommendations proposed; the University should develop and communicate ethical values through ethics seminar, training, colloquium, University should focus on the quality of personnel and professional development programs for both students and faculty, setting good example or role modelling by the faculty and University members. In addition, the study suggests that the curriculum should emphasize in integrating ethics in all subjects taught and the staff code of ethics has to be made more aware to all University members.